Dynamic Economic Dispatch of Power System Network Having Thermal Units and Electric Vehicles using IGWO - Anjali Jain; Ashish Mani; Anwar Siddiqui (Majlesi Journal of Electrical Engineering)
Dynamic economic dispatch (DED) is a complex power system problem. The problem becomes more complex with inclusion of  electric vehicles. In the presented paper,  Improved Grey Wolf Optimizer (IGWO) is proposed to solve this complex problem. IGWO is having a better balance between exploitation and exploration for the complex problem such as  Dynamic Economic Dispatch (DED) taking into account of valve- point effect, transmission losses and ramp-rate limits with and without electric vehicles (EVs). The efficiency of the algorithm is demonstrated on solving different DED problems for 5 generator and 15 generator test systems with and without losses along with different charging profile distribution of electric vehicles.  The results showcased by IGWO is compared with the other algorithm. The results obtained by IGWO algorithm  using repair method adopted in solving dynamic economic dispatch problem is giving competitive results as compared to the results given by other algorithm present in literature.